2020
DOI: 10.1038/s41746-020-0291-x
|View full text |Cite|
|
Sign up to set email alerts
|

Deep learning for automated sleep staging using instantaneous heart rate

Abstract: Clinical sleep evaluations currently require multimodal data collection and manual review by human experts, making them expensive and unsuitable for longer term studies. Sleep staging using cardiac rhythm is an active area of research because it can be measured much more easily using a wide variety of both medical and consumer-grade devices. In this study, we applied deep learning methods to create an algorithm for automated sleep stage scoring using the instantaneous heart rate (IHR) time series extracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 27 publications
0
75
2
Order By: Relevance
“…Recent studies reveal the capability of sleep architecture, in terms of sleep stages and sleep duration, in producing effective technology enabled screening of sleep disorders. Sleep architecture is estimated by leveraging wearable sensors or smartwatches with machine learning methods and its effect on OSA screening is observed in [72,73]. Specifically, stage 1 and stage 3 sleep exhibited anomalous behavior in the case of OSA patients, as stated in [74][75][76].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reveal the capability of sleep architecture, in terms of sleep stages and sleep duration, in producing effective technology enabled screening of sleep disorders. Sleep architecture is estimated by leveraging wearable sensors or smartwatches with machine learning methods and its effect on OSA screening is observed in [72,73]. Specifically, stage 1 and stage 3 sleep exhibited anomalous behavior in the case of OSA patients, as stated in [74][75][76].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent works have shown that ECG can be used as a good predictor of sleep stages based on deep learning classifiers. Sun et al [ 74 ] combined ECG with abdominal respiration and obtained a kappa value of 0.585, while Sridhar et al [ 75 ] obtained a kappa value of 0.66. Combining EEG and ECG measurements has also been proposed in the context of driver drowsiness detection under simulator-based laboratory conditions [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address this need, our first aim for this study was to evaluate the validity of monitoring sleep physiology in ICU patients using easily obtainable biosignals, such as electrocardiogram (ECG) and respiration, using artificial intelligence methods. Although sleep states are commonly discerned through electroencephalogram (EEG) signals, they can also be decoded through analysis of non-EEG signals (25)(26)(27) since sleep modifies a variety of biosignals (28,29), including blood pressure, heart rate, and respiration. Additionally, respiration and ECG measurements are easier to acquire, offer a more practical and repeatable diagnostic tool compared to EEG, and better reflect sleep physiology compared to actigraphy and subjective assessments.…”
Section: Introductionmentioning
confidence: 99%